Gambaran Perawatan Diri pada Pasien Gangguan Jiwa di Yayasan Mentari Hati Kota Tasikmalaya - Kustiawan, Ridwan; Somantri, Iwan; Cahyati, Peni; Oktapiani, Fitri Nur (Neolectura, 2023)
Self-care is self-care is done to maintain good health, both physically and psychologically. No one in four people experienci mental problems in the world, an estimated 450 milion people worldwide who experience mental health disorder (World Health Organization). The purpose of research to describe self-care in patient with mental disorders regarding personal hygiene, ornate, eating, and toileting (defecate or urinate) in the Liver of the Foundation Sun Tasikmalaya City. Self-care deficit is impaired ability to perform activities which consisted of a shower, ornate, eating, and toileting (defecate or urinate) or personal hygiene independently. The method in this research is descriptive. The patient population 200 people with mental disorders, sampling random was 22 people, the type of research instrument used observation sheet, measured by observing the way. The result of self-care personal hygiene of patients with mental disorder category are not good (100%), personal care ornate category are not better than male patients (41%), personal care ornate of the patients were female category was not good (45%), both category (14%), personal care eating the category is not well (91%), while self-care toileting (defecate oe urinate) category is not good (82%). Both category (18%). Self-care deficit mental patients due to a lack of motivation and lack of facilities and infrastructure. All patients with mental disorders self-care deficit, expected to officer foundations to increase motivation and attention to the fulfilment facilities and infrastructure.